2012
DOI: 10.1523/jneurosci.6449-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Dynamics Predict Interindividual Cognitive Differences in Rats

Abstract: There are important and sustained interindividual differences in cognition during aging. Here, we investigated hippocampal spatial representations in a rat model of cognitive aging characterized by individual differences in a mnemonic task. Individual cognitive capabilities in old rats were assessed in a delayed non-matching-to-position task. We recorded hippocampal CA1 place cells as the rats explored a familiar environment. Unlike the usual place cells commonly described in the literature, we found that a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…These findings are consistent with Barnes et al (1997) in which ensembles of CA1 pyramidal cells remapped in 6/6 old rats and 1/6 young adult rats when they were familiar with the environment. Also, McNaughton et al (1996) observed remapping in one young rat between separate recordings on a track that it had over a week of prior experience with, and Hok et al (2012) reported remapping in 2/4 middle-aged rats and 1/4 aged rats in an open field environment in which they had at least 10 days of experience.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with Barnes et al (1997) in which ensembles of CA1 pyramidal cells remapped in 6/6 old rats and 1/6 young adult rats when they were familiar with the environment. Also, McNaughton et al (1996) observed remapping in one young rat between separate recordings on a track that it had over a week of prior experience with, and Hok et al (2012) reported remapping in 2/4 middle-aged rats and 1/4 aged rats in an open field environment in which they had at least 10 days of experience.…”
Section: Discussionmentioning
confidence: 99%
“…Statistics. No statistical methods were used to predetermine sample sizes, but our sample sizes are 508 similar to those reported for place cells in previous studies 7,14 . Statistical tests included Levene's test 509 for equality of variances, two-sample t-test assuming unequal variances, two-sample t-test assuming 510 equal variances, Pearson's correlations and χ² test.…”
mentioning
confidence: 87%
“…In order to assess the remapping events, we performed cross-correlations between the smoothed 443 firing rate maps (using a 5x5 kernel) of the sessions where the same neurons have been identified 444 based on their waveform properties 7 . To be considered as a remapping event the correlation had to 445 fall under a cut-off of r = 0.5 7,8 . 446…”
mentioning
confidence: 99%
“…For example, old rats show differences in the stability of their cognitive maps as assessed by ensemble recordings of hippocampal neurons (Barnes et al, 1997; Schimanski et al, 2013). CA1 hippocampal pyramidal cells in aged rats occasionally generate a new and distinct place cell representation for a familiar environment (Barnes et al, 1997; Schimanski et al, 2013), and these cells take significantly longer to begin to show consistent spatial firing, even in familiar environments (Hok et al, 2012). …”
Section: How Does Aging Affect Our Ability To Compute Online Spatimentioning
confidence: 99%